Supramolecular solvent extraction of bioactive compounds from tamarillo (Solanum betaceum) byproducts - Laura Sofia Torres-Valenzuela; Alfredo Ayala-Aponte; Laura Rodriguez; Ana Rodriguez; Diana Paola Navia-Porras (Discover Food)
Abstract Purpose This study used the eco-friendly SUPRAS extraction technique to recover total phenolic compounds (TPC) and carotenoids from tamarillo byproducts, overcoming the limitations of traditional solvent extraction. Methods In situ extraction with SUPRAS was conducted using two amphiphiles (decanoic acid DA and octanoic acid OA), ethanol, and water. SUPRAS composition was optimized considering the TPC and AA. Results TP exhibited higher TPC, carotenoids, and AA compared to the seed and pulp. The optimal conditions for SUPRAS were: 7.7% DA, 33% ethanol, and 59.3% water, and 8.8% OA, 22% ethanol, and 69.2% water. At these synthesis conditions, TPC were 0.14 and 0.19 gGAE/100 g; 73 and 72% for DPPH scavenging, and 151 and 147 μM TEAC for decanoic acid and octanoic acid-based SUPRAS respectively. The OA increased TPC extraction slightly, while the AA showed the opposite effect. Conclusion SUPRAS demonstrated higher extraction of TPC and AA compared to organic solvents. SUPRAS shows high potential for the extraction of bioactive compounds.